Serial Case: Infarct Stroke In Covid 19 Patients - Retnaningsih, Retnaningsih; Tamad, Fatiha Sri Utami; Tugasworo, Dodik; Andhitara, Yovita; Ardhini, Rahmi; Kurnianto, Aditya (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Introduction: SARS-CoV-2 has been reported to cause various neurological symptoms including stroke. SARS-CoV-2 infection causes the release of cytokines, proinflammatory chemokines, immune system activation, coagulopathy, endothelium, vasculitis, hypoxia, renin-angiotensin system imbalance, and cardiovascular complications, all of which can contribute to stroke. Purpose: Describe the incidence of stroke with different conditions in COVID 19 Cases: There were two cases of stroke infarct in a COVID-19 patient who was admitted to our hospital. Both were treated with a diagnosis of stroke infarct with previous COVID-19 symptoms, the results of laboratory examinations revealed an increase in inflammatory markers in both patients and had been given appropriate treatment according to each patient's condition. But at the end of the treatment one patient died and the other patient went home with clinical improvement. Discussion: The incidence of stroke infarct in this case is thought to be due to several factors, namely the presence of comorbidities in the patient, microvascular thrombus due to the formation of neutrophil extracellular traps (NET), activation of complement which causes thrombogenesis and vasculopathy, formation of antiphospholipid antibodies so that protein c is reduced, the formation of microparticles causes platelet hyperactivation. and increased tissue factor (TF) resulting in hypercoagulation. Adequate therapy in controlling inflammation due to COVID 19 has shown clinical improvement in stroke infarct patients. Conclusion: There are 2 cases of stroke infarction in patients with covid 19 who have comorbidities. The first case with COVID advanced stages experienced a worsening of the condition despite being given appropriate therapy. The second case with COVID middle stages experienced an improvement in the condition after the viral inflammatory factors were controlled and the comorbidity was well controlled.